2017
DOI: 10.1037/vio0000041
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure, PTSD symptoms, and presenting clinical problems among male perpetrators of intimate partner violence.

Abstract: Objective: This study explores trauma exposure, posttraumatic stress disorder (PTSD) symptoms and diagnosis, and PTSD symptom associations with key presenting problems in male intimate partner violence (IPV) perpetrators. The goal is to elucidate the implications of trauma and PTSD for understanding the presenting clinical problems of partner violent men. Method: Male IPV perpetrators (n = 293) at a community-based agency completed assessments of their past traumatic event exposures; current PTSD symptoms; dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
5
45
0
Order By: Relevance
“…We will also benefit from a review of surviving children's perspectives on change in their father, a review of practitioners' perspectives, and a review of quantitative studies of the correlates of change. The current review authors call for further syntheses, systematic reviews, and experimental evaluation of interventions, and we would align ourselves with a growing body of researchers in this field (Grych & Swan, 2012;Murphy, 2013;Semiatin, Torres, LaMotte, Portnoy, & Murphy, 2017;Sullivan, 2013) who call for a more systematic approach to perpetrator program development.…”
Section: Resultsmentioning
confidence: 98%
“…We will also benefit from a review of surviving children's perspectives on change in their father, a review of practitioners' perspectives, and a review of quantitative studies of the correlates of change. The current review authors call for further syntheses, systematic reviews, and experimental evaluation of interventions, and we would align ourselves with a growing body of researchers in this field (Grych & Swan, 2012;Murphy, 2013;Semiatin, Torres, LaMotte, Portnoy, & Murphy, 2017;Sullivan, 2013) who call for a more systematic approach to perpetrator program development.…”
Section: Resultsmentioning
confidence: 98%
“…Examining more proximal factors potentially stemming from ACEs, namely trauma symptoms, is an important evolution for IPV intervention. The current study sample reported profoundly higher prevalence rates of clinical levels of PTSD symptomology (31.1%) compared with studies with more White, socioeconomically advantaged men in the general population (3.2%; Hahn et al, 2015), military population (2–17%; Creamer, Wade, Fletcher, & Forbes, 2011), and clinical samples of BIPs (10–13.6%; Rosenbaum & Leisring, 2003; Semiatin, Torres, LaMotte, Portnoy, & Murphy, 2017), adding to the limited body of trauma research with marginalized populations (e.g., Hoyt, Wray, Wiggins, Gerstle, & Maclean, 2012). Men in the study also reported severe complex trauma symptoms in the past month.…”
Section: Discussionmentioning
confidence: 97%
“…Holtzworth-Munroe and Stuart [ 34 ] argue that perpetrators can be classified using three characteristics: severity/frequency of aggression, how general the aggression is (within-family only or not), and degree of perpetrator pathology. In addition to a focus on personality disorders in perpetrators, hundreds of studies have found a link between aggressive behaviors (both within and outside of intimate relationships) and post-traumatic stress disorder (PTSD; [ 35 , 36 , 37 , 38 ]).…”
Section: Four Levels Of Influencementioning
confidence: 99%